KF/Al2O3/PEG-400: An Efficient Catalytic System for the Fiesselmann-Type Synthesis of Thiophene Derivatives - Bezboruah, Pranjal; Gogoi, Pranjal; Gogoi, Junali; Boruah, Romesh C. (Synthesis, 2013)
A simple and mild protocol has been developed for the synthesis of novel steroidal and nonsteroidal thiophene derivatives from β-halo-α,β-unsaturated aldehydes using KF/Al2O3/PEG-400 as an efficient catalytic system. The β-halo-α,β-unsaturated aldehydes are synthesized from the corresponding ketones using Vilsmeier formylation reaction and converted into β-halo-α,β-unsaturated nitriles. The synthetic protocol is subsequently applied to the synthesis of 3-aminothiophene derivatives using β-halo-α,β-unsaturated nitriles.
Keywords: Fiesselmann synthesis; KF/Al2O3/PEG-400; thiophene; unsaturated aldehyde; unsaturated nitrile